Evaluation of self medication practices and prescription patterns in patients of chronic kidney disease: A cross-sectional, questionnaire based study - Raakhi K Tripathi; Chaitali Pilliwar; Snehalata V. Gajbhiye; Sujeet K. Bhilwade; Tukaram Jamale (Perspectives in Clinical Research)
Background: Pharmacotherapy of chronic kidney disease (CKD) consists of prescribing myriad of drugs such as antihypertensives, antidiabetics, and phosphate binders to delay disease progression and control the comorbidities, resulting in inherent variability in prescriptions. In addition, tendency to self-medicate may further aggravate the condition. Hence, the present study was planned to assess self-medication practices and variability in prescription patterns in CKD patients. Methodology: A cross-sectional, questionnaire-based study approved by the ethics committee was conducted in CKD patients attending the nephrology outpatient department. The prescription details which included drug name, dosage form, dose, frequency, duration, and dosage instructions were recorded and prescription completeness was checked. To assess the tendency of CKD patients to self-medicate, each patient was administered a prevalidated [Content Validity Ratio (CVR) = 0.76] 8-item questionnaire which had dichotomous responses “Yes” and “No” and was scored as 2 and 0, respectively (total score 16). Results: Three hundred CKD patients (150 on hemodialysis and 150 nondialysis) yielded 300 prescriptions with 1272 drugs. It was evident that 33% of patients did self-medicate themselves with analgesics, and the mean score (7.81 ± 3.01) of self-medication practices was perceived significantly higher in the nondialysis group (8.41 ± 3.46). The most common classes of drugs prescribed in CKD patients were calcium channel blockers (41%), antidiabetic drugs (39%), diuretics (35%), gastrointestinal drugs (35%), and multivitamins (27%), with the average number of drugs being 5.84 ± 0.51. Conclusion: Nearly one-third of CKD patients were self-medicating with paracetamol, nonsteroidal anti-inflammatory drugs; more in the nondialysis group emphasizing reinforcement of patient education programs. The most common drugs prescribed were amlodipine, followed by metformin, and the average number of drugs was less in our setting, indicating vigilant dose prescribing in CKD patients.